The Effect of Antiretroviral Therapy (ART) Duration on CD4 Counts in Human Immunodeficiency Virus (HIV) Patients in dr. Doris Sylvanus Regional Hospital - Oberson Nainggolan; Lia Sasmithae; Ratna Widayati (Fakultas Kedokteran Universitas Brawijaya, 2023)
Human Immunodeficiency Virus (HIV) attacks white blood cells, thereby reducing the immunity of infected patients. It attacks Cluster of Differentiation 4 (CD4) lymphocyte cells which have a role in the immune system. It has killed 36.3 million people worldwide. There were reported 222 cases in Central Kalimantan Province in 2019. The therapy given to suppress HIV is antiretroviral (ARV) which gradually recover CD4 cells of the patients. This study aims to determine the effect of duration of the antiretroviral therapy (ART) duration on CD4 counts in patients with HIV at the VCT (Voluntary, Counselling, and Test) Polyclinic, dr. Doris Sylvanus Hospital during 2019-2020. It is a descriptive retrospective study, extracting data from patients medical record data. Following total sampling and selected based on inclusion and exclusion criteria i.e. aged ≥18 years and diagnosed with HIV during 2019-2020, with complete CD4 count records prior and after ART, there were 45 patients included. The results showed that CD4 counts increased in patients with fixed dose combination (FDC) Tenofovir, lamivudine and efavirenz, with average value of 190.36± 220.92 cells/mm3 prior ART, became 259.93± 203.74 cells/mm3 at 12 month ART, and 310.82± 22.,53 cells/mm3 at 24 month ART (p = 0.000). Thus, the longer ART duration the higher CD4 counts and recover the normal range.